3/4-5/6x=1/3
giúp em với
Hãy nhập câu hỏi của bạn vào đây, nếu là tài khoản VIP, bạn sẽ được ưu tiên trả lời.
c: Ta có: \(\left(x+1\right)^2\ge0\forall x\)
\(\left(y-\dfrac{1}{3}\right)^2\ge0\forall y\)
Do đó: \(\left(x+1\right)^2+\left(y-\dfrac{1}{3}\right)^2\ge0\forall x,y\)
\(\Leftrightarrow\left(x+1\right)^2+\left(y-\dfrac{1}{3}\right)^2-10\ge-10\forall x,y\)
Dấu '=' xảy ra khi x=-1 và \(y=\dfrac{1}{3}\)
a: \(A=\dfrac{2\cdot8^4\cdot27^2+44\cdot6^9}{2^7\cdot6^7+2^7\cdot40\cdot9^4}\)
\(=\dfrac{2\cdot2^{12}\cdot3^6+2^2\cdot11\cdot2^9\cdot3^9}{2^7\cdot3^7\cdot2^7+2^7\cdot2^3\cdot5\cdot3^8}\)
\(=\dfrac{2^{13}\cdot3^6+2^{11}\cdot3^9\cdot11}{2^{14}\cdot3^7+2^{10}\cdot5\cdot3^8}\)
\(=\dfrac{2^{11}\cdot3^6\left(2^2+3^3\cdot11\right)}{2^{10}\cdot3^7\left(2^4+5\cdot3\right)}\)
\(=\dfrac{2\cdot301}{3\cdot31}=\dfrac{602}{93}\)
\(4A-3x^2+7-6x=x^2+3A-4x-3\)
\(\Rightarrow4A-3A=\left(x^2+3x^2\right)-\left(4x-6x\right)-\left(3+7\right)\)
\(\Rightarrow A=4x^2-\left(-2x\right)-10\)
\(\Rightarrow A=4x^2+2x-10\)
\(a,\left|2x+\dfrac{1}{2}\right|=0\\ \Leftrightarrow2x+\dfrac{1}{2}=0\\ \Leftrightarrow2x=-\dfrac{1}{2}\\ \Leftrightarrow x=-\dfrac{1}{4}\\ b,\left|3x+\dfrac{3}{4}\right|=3\\ \Leftrightarrow\left[{}\begin{matrix}3x+\dfrac{3}{4}=3\\3x+\dfrac{3}{4}=-3\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}3x=\dfrac{9}{4}\\3x=-\dfrac{15}{4}\end{matrix}\right.\\ \Leftrightarrow\left[{}\begin{matrix}x=\dfrac{3}{4}\\x=-\dfrac{5}{4}\end{matrix}\right.\)
Sửa đề: -24x^2y^3
9x^4-24x^2y^3+16y^6
=9x^4-2*3x^2*4y^3+16y^6
=(3x^2-4y^3)^2
Bài 1:
a) \(x\left(x+1\right)+x\left(x-1\right)-2x^2\)
\(=x^2+x+x^2-x-2x^2\)
\(=2x^2-2x^2\)
\(=0\)
b) \(\left(x+2\right)\left(x^2-x+1\right)-\left(x-2\right)\left(x^2+x+1\right)\)
\(=x^3-x^2+x+2x^2-2x+2-x^3-x^2-x+2x^2+2x+2\)
\(=\left(x^3-x^3\right)+\left(-x^2+2x^2-x^2+2x^2\right)+\left(x-2x-x+2x\right)+\left(2+2\right)\)
\(=2x^2+4\)
c) \(\left(3-x\right)^2+2\left(x-3\right)\left(x+7\right)+\left(x+7\right)^2\)
\(=\left(x-3\right)^2+2\left(x-3\right)\left(x+7\right)+\left(x+7\right)^2\)
\(=\left[\left(x-3\right)+\left(x+7\right)\right]^2\)
\(=\left(x-3+x+7\right)^2\)
\(=\left(2x+4\right)^2\)
5/6x=3/4-1/3=5/12
x=5/12/5/6=1/2
\(\frac{3}{4}\)-\(\frac{5}{6}\)x=\(\frac{1}{3}\)
\(\frac{5x}{6}\)=\(\frac{3}{4}\)-\(\frac{1}{3}\)
\(\frac{5x}{6}\)=\(\frac{5}{12}\)
5x=\(\frac{5}{12}\).6
5x=\(\frac{5}{2}\)
x=\(\frac{5}{2}\):5
x=\(\frac{1}{2}\)
Vậy x=\(\frac{1}{2}\)
Chúc em học tốt^^